Federal disaster mental health response and compliance with best practices - McIntyre, Jody May (Kansas State University, 2009)
The purpose of this study was to review state disaster mental health response plans and actual disaster mental health responses to examine not only adherence to identified disaster mental health best practices, but also to highlight procedures being performed during deployment of disaster mental health response teams. This research study was developed to gain a thorough understanding of disaster mental health response in both the planning and implementation phases. Interviews with three state disaster mental health officials were completed and a review of each state’s disaster mental health state plan was completed. The study investigated the conclusiveness of state plans and their adherence to published best practices in three post 9/11 disasters: 2005 Hurricane Katrina response in Mississippi; 2007 Greensburg, Kansas tornado; and 2008 Indiana flooding. A phenomenological approach was used to identify themes in disaster mental health response that should be considered for future disaster mental health planning. Each state’s disaster mental health plan varied in compliance to identified best practices; however, it was noted that all states were more compliant to best practices in their response than in the written state disaster mental health state plan. Several themes for disaster mental health responses were identified that were not previously fully addressed in the published best practices. Such themes addressed issues in disaster mental health teams and training, local disaster mental health response, communication, research and data collection, relationships with external organizations, and long-term recovery. This research may serve as a guide for those developing disaster mental health plans and encourage further considerations in disaster mental health response.
Keywords: Mental Health; Disaster; Health Sciences, Mental Health (0347)